SOSIALISASI ORANG TUA TENTANG PERAN GENDER PADA ANAK USIA DINI DI DESA SUNGAI KUNYIT LAUT KABUPATEN MEMPAWAH - Pramudya Hadista Priyandanu; Maria Ulfah; Izhar Salim (Universitas Tanjungpura, 2020)
AbstractThis study entitled “Parent’s Socialization ofGender Roles in Early ChildhoodVillage of Sungai Kunyit Laut MempawahDistrict”. The goal was to know the parent’s socialization of gender roles in earlychildhoodthrough primary socialitazion and secondarysocialization.There were two sub-problems, 1) How is the parent’s socialization of gender roles through primary socialization in early childhood at Village of Sungai Kunyit ?and 2) How is the parent’s socialization of gender roles through secondary socialization in early childhood at Village of Sungai Kunyit ?. The method of research uses a qualitative approach with descriptive methods. The source of research data was the parents and childrens who play their roles that are not appropriate for their gender. The Data collections techniques through interviews, observations, and documentations. The analysis of research was presented in qualitative descriptive and using seven informant. The results of research was divided in two; 1)There’s imperfection of socialization on primary socialization, where’s childrens are facilitated with things that didn’t matching with their gender. 2) There’s imperfection of socialization on secondary socialization, childrens playing their roles that is opposite of their gender while their playing on their environment and lack of parental attention to their childrens in their environment, so that childrens commiting gender deviations while their playing in their environment. Keywords: Early Childhood, Gender Roles, Socialization.